2016
DOI: 10.1038/mtna.2016.101
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Generation of Orthologous Point Mutations in Pigs via CRISPR-assisted ssODN-mediated Homology-directed Repair

Abstract: Precise genome editing in livestock is of great value for the fundamental investigation of disease modeling. However, genetically modified pigs carrying subtle point mutations were still seldom reported despite the rapid development of programmable endonucleases. Here, we attempt to investigate single-stranded oligonucleotides (ssODN) mediated knockin by introducing two orthologous pathogenic mutations, p.E693G for Alzheimer's disease and p.G2019S for Parkinson's disease, into porcine APP and LRRK2 loci, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 53 publications
6
24
0
Order By: Relevance
“…It has been shown in human cells that NGA PAMs may have up to 40% activity in some loci 74 , 75 . Interestingly, we also observed that some clones contained the 535A > T substitution on only one allele while the PAM mutation was present on the two alleles suggestive of partial or incomplete HDR and has been reported by others 27 , 31 , 35 . This may be indicative of a cut-to-distance dependence mechanism in the incorporation of single nucleotide edits in chicken PGCs as previously reported in human cells and mouse zygotes 27 , 35 .…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown in human cells that NGA PAMs may have up to 40% activity in some loci 74 , 75 . Interestingly, we also observed that some clones contained the 535A > T substitution on only one allele while the PAM mutation was present on the two alleles suggestive of partial or incomplete HDR and has been reported by others 27 , 31 , 35 . This may be indicative of a cut-to-distance dependence mechanism in the incorporation of single nucleotide edits in chicken PGCs as previously reported in human cells and mouse zygotes 27 , 35 .…”
Section: Discussionsupporting
confidence: 86%
“…The RAD51 stimulatory compound RS-1 increased knock-in efficiency in rabbit embryos (from 4.4 to 26.1%) 18 , HEK cells (from 3.5 to 21%) 17 and U2OS cells (from 1.9 to 2.4%) 17 , but not in hiPSCs 19 . No effect of RS-1 on TNS efficiency was found in porcine fetal fibroblasts 23 . Furthermore, We tested these molecules in iPSC lines that we generated that carry doxycycline-inducible Cas9 (iCRISPR-Cas9) and Cas9 nickase with the D10A mutation (iCRISPR-Cas9n) integrated in their genomes 11 .…”
mentioning
confidence: 83%
“…Genome editing conducted by this mechanism can be used to insert a predefined single nucleotide or sequence, or even change or delete it in existing genes. After the first knockouts births reported by NHEJ, successful generation of knock-in large animals by HDR were achieved in sheep [15,16], goats [17] and pigs [18].…”
Section: Introductionmentioning
confidence: 99%